Nations on display. Nation branding strategies and their implementation in national pavilions : the cases of Finland and the Kingdom of Saudi Arabia - Rissanen Annika (2024)
This thesis aims to explore the policies and approaches to nation branding that states develop to promote their international image. This goal is achieved through analytical focus on two cases: Finland and Saudi Arabia. The thesis seeks to explore how Finland and Saudi Arabia define, frame, and develop the tasks of establishing a favorable international image of themselves as strategic activity. The analysis draws on theoretical and conceptual discussion of nation branding and public diplomacy and employs the methods of contents analysis and aesthetic and narrative analysis while taking as its research material the official publications of Finland: ‘Finland’s Country Branding Strategy’ (2017) and ‘Handbook for Country Image Work’ (2024), and of Saudi Arabia: ‘Vision 2030’, and the national pavilions of the two. Based on the findings of its analysis, the thesis argues that there is no ‘one’ successful model of nation branding strategy – no one-size-fits-all approach to nation branding. Rather, the thesis concludes that successful nation branding requires cooperation between the government and relevant stakeholder groups, the recognition of the nation’s position in relation to its regional neighbours, and multi-channel communication. I conclude that states identify their strengths, weaknesses and target groups in order to create a distinctive nation brand.